The Kosher Capones : A History of Chicago's Jewish Gangsters - Kraus, Joe, 1965- (Book collections on Project MUSE., 2019)
"The Kosher Capones tells the story of Chicago's Jewish gangsters from Prohibition into the 1980s"--